2010
DOI: 10.1002/ajmg.a.33139
|View full text |Cite
|
Sign up to set email alerts
|

Birth incidence and prevalence of tumor‐prone syndromes: Estimates from a UK family genetic register service

Abstract: Autosomal dominantly inherited tumor-prone syndromes are a substantial health problem and are amenable to epidemiologic studies by combining cancer surveillance registries with a genetic register (GR)-based approach. Knowledge of the frequency of the conditions provides a basis for appropriate health-resources allocations. GRs for five tumor-prone syndromes were established in the Manchester region of North West England in 1989 and 1990. Mapping birth dates of affected individuals from families onto regional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
505
0
22

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(561 citation statements)
references
References 33 publications
9
505
0
22
Order By: Relevance
“…Affecting as many as 1 in 2700 newborns [61], neurofibromatosis type 1 (NF1) is a monogenic disorder characterized by both physical and cognitive symptoms. Hallmarks of the syndrome include café-au-lait spots and benign nerve tumors known as neurofibromas.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…Affecting as many as 1 in 2700 newborns [61], neurofibromatosis type 1 (NF1) is a monogenic disorder characterized by both physical and cognitive symptoms. Hallmarks of the syndrome include café-au-lait spots and benign nerve tumors known as neurofibromas.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…Neurofibromatosis type 1 (NF1) is a relatively common autosomal dominant neurocutaneous disorder with an estimated birth incidence of 1/2,700 (Evans et al, 2010). Approximately 40% to 50% of the cases are caused by a de novo mutation in the NF1 gene (Evans et al, 2010; Friedman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% to 50% of the cases are caused by a de novo mutation in the NF1 gene (Evans et al, 2010; Friedman, 1999). Clinical features of NF1 include multiple café‐au‐lait spots, axillary and inguinal freckling, multiple cutaneous neurofibromas, and iris Lisch nodules (NIH, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Exonic, multiexonic, and whole-gene deletions have been reported in about 6% of individuals with NBCCS [Evans and Farndon, 2002]. The studies of disease prevalence come from the UK population, where it is nearer to 1:30,827 [Evans et al, 2010]; The actual figure could be higher still, since less severe cases may not be diagnosed and Jones et al [2011] recently reported an incidence of 1 in 19,000 births.…”
Section: Introductionmentioning
confidence: 99%
“…Exonic, multiexonic, and whole-gene deletions have been reported in about 6% of individuals with NBCCS [Evans and Farndon, 2002]. The studies of disease prevalence come from the UK population, where it is nearer to 1:30,827 [Evans et al, 2010]; The actual figure could be higher still, since less severe cases may not be diagnosed and Jones et al [2011] recently reported an incidence of 1 in 19,000 births.NBCCS is clinically diagnosed in patients with one major diagnostic criterion and molecular confirmation or two major criteria or one major and two minor diagnostic criteria [Bree et al, 2011]. The major criteria are the following: (1) BCC before the age of 20 or excessive numbers of BBCs out of proportion to prior sun exposure and skin type, (2) odontogenic jaw keratocyst prior to 20 years of age, (3) palmar or plantar pitting, (4) lamellar calcification of the falx cerebri, (5) medulloblastoma typically desmoplastic, and (6) first-degree relative with NBCCS.…”
mentioning
confidence: 99%